1969
DOI: 10.1139/g69-037
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture of Wheat Tissues. I. Callus Formation, Organ Redifferentiation and Single Cell Culture

Abstract: Callus induction, organ formation from callus and single callus cell culturc have bcen tried in wheat. Though lcinetin sl~owed no effects, supplemcnts of 2,4-1) (I-lOnig/l) or IAA (jOmg/l) to tlie basal mcdia induced calluses from seedling roots of einl~orn, enlmcr and coninion wtlcats, and from stem pieccs of common \vheat. T h e best caIIus gron;th was olxained when casein liydroIysate ( l g / l ) or coconut milk (1%) was added t o tlic basal media. Callus gl.owtIi n.as also vigorous when 2,4-11 (0.5-2.0rng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…The chromosome constitution of four year-subcultured callus cells which originated from the root of common wheat, was similar to that of one year-subcultured callus cells, whose chromosome number varied from 26 to 84 with predominantly diploid cells (Shimada et al 1969). The present results clearly show that the callus cell population of wheat does not greatly change its chromosome constitution due to continuing subculture.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The chromosome constitution of four year-subcultured callus cells which originated from the root of common wheat, was similar to that of one year-subcultured callus cells, whose chromosome number varied from 26 to 84 with predominantly diploid cells (Shimada et al 1969). The present results clearly show that the callus cell population of wheat does not greatly change its chromosome constitution due to continuing subculture.…”
Section: Resultssupporting
confidence: 66%
“…The chromosome constitution of callus cells originating from the stem of a common wheat, Triticum aestivum cv. S-615, was also similar to constitutions of callus (Shimada et al 1969) . Therefore, we concluded that, regardless of the source, i.e.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 1 shows normal and telocentric chromosomes. Variations of chromosome constitutions in common wheat calluses were previously reported (Shimada et al 1969;Asami et al 1972;Shimada et el. 1974;Asami et al 1975;Inomata et a1.1975) .…”
Section: Resultsmentioning
confidence: 61%
“…It has already been known that chromosome constitutions vary greatly in callus tissues (De Torok and White 1960;De Torok and Roderick 1962;Cooper et al 1964;Nishiyama and Taira 1966;Shimada and Tabata 1967;Heinz et al 1969;Shimada et al 1969;Asami et al 1972;Bayliss 1973;Asami et al 1975). Structural changes of chromosomes in cultured callus cells were previously reported by Kao et al (1970).…”
mentioning
confidence: 89%